STUDY ON DYNAMIC CHARACTERISTICS OF MOTORIZED SPINDLE SYSTEM UNDER BEARING PRELOAD - GAO Feng; JIA WeiTao; LI Yan; ZHANG DongYa; CHENG MingKe; WU WenWu (Jixie qiangdu)
Considering the influence of the nonlinear factor of bearing preload on the dynamic stiffness of bearing support,a dynamic model of grinding motorized spindle system is established. Considering the unbalanced force caused by the eccentricity of the rotor mass in the rotor system,the numerical integration method is used to study the nonlinear dynamic behavior of the motorized spindle rotor system under different preload and rotating speeds. The results show that the bearing preload is an important factor affecting the nonlinear dynamic characteristics of the motorized spindle rotor system. Rational selection of the operating parameters of the rotor system can improve the stability of the system.